KRUSTPILS DZIRKAĻI HILLFORT. NEW INSIGHTS - Urtāns, Juris (Via Latgalica, 2017)
Dzirkaļi Hillfort is situated at Dzirkaļi, Kūku parish in Krustpils region. The Hillfort was first mentioned in records in 1925; in 1928, Ernests Brastiņš published a more comprehensive description and survey of the Hillfort (Fig. 1). Due to handmade pottery sherds with smooth and plastered surface accidentally found in the outcrops of the cultural layer, the population of the Hillfort could be dated with the I millennium AD. Dzirkaļi Hillfort in its highday might have been a centre of the region. Less than 100 years ago, there were fields of Dzirkaļi village both on the plateau of the Hillfort and at its foot. Legends are known about Dzirkaļi Hillfort as a site of a sunken castle and buried treasure, which is haunted by ghosts. Dzirkaļi Hillfort had been fixed up on a branch of a hill that sharply ends against swampy lowland. The northern slope of the Hillfort, which overlooks the swampy lowland and is 14 m high, had been additionally fortified with a terrace, but on the southern side more profound fortification work was carried out in olden times; here the hill had been marked off with a deeply dug-up rampart and barred with a 1.5 m high wall built by people, which is separated by another ditch from the artificially smoothed and slanting plateau of the Hillfort. On both sides of the Hillfort, terraces had been built to make the slopes even steeper. At the northern and eastern foot of the Hillfort appropriate cultural layer of settlement corresponding to the Hillfort has been found, but to west of the Hillfort, Baznīckalns (“Church Hill”) is situated, where a sanctuary of the inhabitants of the Hillfort might have been. At the northwestern foot of the Hillfort, Naudas avots (“Money Spring”) had been situated, which might have served as the source of water for the inhabitants and has been mentioned in legends. Several ancient burial sites are known to be situated near the Hillfort, as well as features of ancient fields, places of roads, sites of separate buildings and other evidence of olden times (Fig. 2–5). In 2014, the first systematic archaeological excavations were carried out in the Hillfort, guided by Juris Urtāns, an archaeologist and the owner of the Hillfort (Fig. 6). The northeastern side of the Hillfort plateau was chosen as investigation site. On exploring the excavation site (3×8 m), it turned out that the upper layer in the depth of 0.30–0.40 m had been mixed by ploughing the plateau of the Hillfort. Subsoil nearer the centre of the plateau was uncovered in the depth of 0.55 m, nearer the edge of the plateau – 0.95 m deep. No marked evidence of structures was discovered, except for a couple of dints in the subsoil – possibly places were posts had been. The cultural layer is comparatively even; only fist-sized and smaller stones were found in it. At the end of the site, towards the edge of the plateau, the former cultural layer was covered by about 20 cm thick layer of sand. The whole dug-up cultural layer was sifted through sieves, and a great quantity of pottery sherds (811 fragments have been listed) were recovered. Few antiquities have been found and they are not very distinctive: a tip of an iron knife, tiny bronze rings, possibly, a fragment of iron arrowhead, ground stones, and flint chips. Pottery, which is represented mostly by tiny fragments, recovered as a result of sifting, basically belongs to handmade smooth, plastered, pinched and scratched pottery; however, fragments of early wheel pottery have been found as well (Fig. 7; defined by Baiba Dumpe). This fact allows to expand and specify the previously assumed dating of Dzirkaļi Hillfort and to conclude that population of Dzirkaļi Hillfort can be dated with the I millennium AD; however, handmade scratched pottery and wheel pottery permit that the Hillfort had been populated also BC and at the very beginning of the II millennium AD. In 2014, a hillock (7–8 m across, height 0.6 m) about 300 m southeast from the Hillfort was archaeologically investigated under Elīna Guščika’s guidance (Fig. 8). The hillock resembled ancient burial mound, but, when it was dug up, no evidence of ancient burial was discovered, although several signs characterising the tradition of barrows were stated. Radiocarbon dating of coal found in the hillock allowed concluding that fire had burned there during the early period of the existence of the Hillfort – the last centuries before our era. After investigation, the hillock was restored to its original visual state. From the eastern side leading to the Hillfort there is a road cut into the relief, which, judging by the tall trees grown on it, has not been used at least for the last fifty years. This road marks itself about 300 m from the Hillfort. At first the road is hardly discernible on the gently sloping side, but when the slope gets steeper, especially at the break of the slope, the road has cut itself about half a metre into the side of the hill and is approximately three or four metres wide. This testifies that the road had been used by carts and probably also by sledges. The notch of the road can be traced as far as about 100 metres. On the most pronounced point of relief break, parallel to the cart road, another site of road was observed, 10–15 m in length, which might be identified as a path for riders or horses. This is a ditch-like deepening, less than one metre deep, with a pronounced wedge-like section. During the last years a number of such riders’ or groove paths have been discovered in Latvia, but their investigation has hardly been started. Regarding the case of Dzirkaļi, it can be said with assurance that the riders’ holloway leads to the Hillfort, therefore it could be associated with the Hillfort and the period when the castle existed.